Implementasi Metode Ummi dalam Pembelajaran Al-Qur’an di SDIT Insan Qur’ani Bener Meriah - Ghani, Abdul (Jurnal Ilmiah Guru Madrasah, 2025)
This study aims to analyze the implementation and effectiveness of the Ummi Method in Quran learning at SDIT Insan Qurani Bener Meriah. The Ummi Method is an innovative approach that emphasizes the principles of tartil (proper recitation), talaqqi (direct teacher-student transmission), and tasmi' (listening assessment) with an affectionate approach akin to a mother's teaching. The research used a descriptive qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews with the school principal, Quran coordinator, teachers, and students, as well as documentation studies. The results show that the implementation of the Ummi Method was carried out systematically through three main stages: (1) preparation stage through teacher training and certification; (2) implementation stage with seven structured learning phases; and (3) continuous evaluation stage. The implementation of this method proved to significantly improve students' Quran recitation quality, enhance makhraj and tajwid aspects, and foster love for the Quran. The main constraints included limited certified teachers and heterogeneous student abilities, which were successfully addressed through classical approaches and regular mentoring programs. This study concludes that the Ummi Method is effective in improving elementary school students' Quran reading competence and can be adopted as an innovative alternative learning model.